Investigations into the ecology of a population of Citrus Red Scale (Aonidiella aurantii Mask.) in the Swaziland lowlands - Atkinson, P R (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1982)
In the Swaziland lowlands, biological control of the citrus pest red scale, Aonidiella aurantii (Mask), has been consistently unsuccessful although it is successful in middle altitude regions. However, recent cases of resistance to organophosphate insecticides elsewhere in southern Africa, make it important to reconsider biological control of red scale in the lowlands. Should similar resistance be evolved in this region, the pest could be controlled only by natural means together with oils. This account attempts to answer questions about the natural control of a red scale population in the lowlands, by examining data collected between 1972 and 1975. The population was continuously breeding with overlapped generations. It consisted of three sections, on leaves, twigs and fruit, having different rates of reproduction, development and mortality. These sections are considered separately but that on leaves, being relatively unimportant, is largely ignored. The generation mortality is estimated in the sections on twigs and fruit and related to climatic and biotic indices. The causes of seasonal and between-years variation in the sections on twigs and fruit are elucidated. The effectiveness of each kind of natural enemy is examined and the factors affecting natural enemy numbers are investigated. The question of population regulation is discussed. Differences in mean infestation levels in middle altitude and lowland regions are explained in terms of different rates of reproduction and mortality.
Keywords: Citrus -- Diseases and pests -- Africa, Southern